The nature of legislative intent - Ekins, Richard (Oxford : Oxford University Press, 2013)
The idea of legislative intent plays a central role in legal interpretation and constitutional theory, yet is repeatedly challenged as being an illusion. This book develops a robust account of how and why legislatures form intentions, and the importance of these intentions to understanding law and parliamentary democracy.
Description based on online resource; title from PDF title page (viewed on Oct. 30, 2012).
Keywords: Bill drafting; Law -- Interpretation and construction